Inisiasi Program Membangun Ekonomi Kreatif dalam Meningkatkan Kesejahteraan Kehidupan Masyarakat Desa Tanjung Karang Kabupaten Gorontalo Utara di Era Pandemi Covid 19 - Zuchri Abdussamad (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
economic concept in the new economic era that intensifies information and creativity by relying on ideas, knowledge, skills and talents, rather than human resources. Therefore, Human Resources (HR) as the main production factor in its economic activities. So that knowledge is needed about self potential and the local cultural environment, from the residents of each village/village/city as a source of life and a place to live.With the large-scale social restrictions (PSBB), especially now the Gorontalo Provincial government will enter the scope of the Implementation of the Implementation of Micro Community Activity Restrictions (PPKM) starting June 1, 2021. So that the recommendation to stay at home, the community will not be able to find income especially for the community whose work is paid daily, surely they will be greatly affected.Departing from the partner problem, the solution offered in this community service is that together with the community will carry out Community Service Thematic Village Development in the form of Initiating a program to build a creative economy in improving the welfare of the people of Tanjung Karang village, North Gorontalo Regency in the era of the COVID-19 pandemic.